Mirando hacia el interior: Problemática regulatoria de la propiedad comunal en el Perú y su relación con los recursos naturales, la preservación y el ejercicio de sus derechos - Ravina Sánchez, Raúl (2024)
This work is intended to describe an important part of the regulatory problems on common land in Peru. To this end, we hypothesize that there are various issues that the regulatory framework and procedures in force do not allow to guarantee the rights of peasant communities and the proper use of their lands. To confirm our hypothesis, we will analyze the following issues related to the regulation of common land: i) relationship with natural resources, ii) lack of demarcation and titling, iii) overlapping of rights, iv) update of registers, statutes and boards of directors, v) high number of members that complicates to make agreements, vi) usufruct rights and individual adjudication within the community.To develop some of the problems identified we have reviewed real cases which will be used as examples to represent the situation of the system.